African linguistics across the disciplines Selected papers from the 48th Annual Conference on African Linguistics - Lotven, Samson; Bongiovanni, Silvina; Weirich, Phillip; Botne, Robert; Gyasi Obeng, Samuel (Contemporary African Linguistics, 2019)
Since the hiring of its first Africanist linguist Carleton Hodge in 1964, Indiana University's Department of Linguistics has had a strong and continuing presence in the study of African languages and linguistics through the work of its faculty and of its graduates on the faculties of many other universities. Research on African linguistics at IU has covered some of the major language groups spoken on the African continent. Carleton Hodge's work on Ancient Egyptian and Hausa, Paul Newman's work on Hausa and Chadic languages, and Roxanna Ma Newman's work on Hausa language structure and pedagogy have been some of the most important studies on Afro-Asiatic linguistics. With respect to Niger-Congo languages, the work of Charles Bird on Bambara and the Mande languages, Robert Botne's work on Bantu structure (especially tense and aspect), Samuel Obeng and Colin Painter's work on Ghanaian Languages (phonetics, phonology, and pragmatics), Robert Port's studies on Swahili, and Erhard Voeltz's st